Études helléniques / Hellenic Studies - Coufoudakis, Van (Études helléniques / Hellenic Studies, 1997)
This volume of Études helléniques / Hellenic Studies summarises the post-1974 intellectual debate in Greece on the direction and objectives of Greek foreign policy. lt also contains articles assessing post-1974 Greek foreign policy and provides insights into policies vis-à-vis the European Union, Balkans and United States. Other essays evaluate the influence of Constantine Karamanlis on post-1974 Greek foreign policy, and the risks of a Greco-Turkish confrontation.